De zonvloed an interview with John D. Morris Phd. - Morris, John D.; Van den Bosch, Jan (El Cajon, Calif. : Institute for Creation Research, 1988)
Dr. John D. Morris discusses The Deluge and Noah's Ark from an evangelistic point of view
' Film on Mt. Ararat and the nearby villages of Eastern Turkey ...'
' Released by ICR as' The Deluge''
Film editor, Tom Metz
Keywords: Deluge; Bible and science; Ararat, Mount (Turkey)